Environmental factors shape sleep EEG connectivity during early adolescence - Marković, Andjela; Kaess, Michael; Tarokh, Leila (Cerebral cortex, 2020)
Abstract. Quantifying the degree to which genetic and environmental factors shape brain network connectivity is critical to furthering our understanding of the